High-Performance Single-Crystalline Arsenic-Doped Indium Oxide Nanowires for Transparent Thin-Film Transistors and Active Matrix Organic Light-Emitting Diode Displays - Chen, Po-Chiang; Shen, Guozhen; Chen, Haitian; Ha, Young-geun; Wu, Chao; Sukcharoenchoke, Saowalak; Fu, Yue; Liu, Jun; Facchetti, Antonio; Marks, Tobin J; Thompson, Mark E; Zhou, Chongwu (ACS nano, 2009)
We report high-performance arsenic (As)-doped indium oxide (In2O3) nanowires for transparent electronics, including their implementation in transparent thin-film transistors (TTFTs) and transparent active-matrix organic light-emitting diode (AMOLED) displays. The As-doped In2O3 nanowires were synthesized using a laser ablation process and then fabricated into TTFTs with indium−tin oxide (ITO) as the source, drain, and gate electrodes. The nanowire TTFTs on glass substrates exhibit very high device mobilities (∼1490 cm2 V−1 s−1), current on/off ratios (5.7 × 106), steep subthreshold slopes (88 mV/dec), and a saturation current of 60 μA for a single nanowire. By using a self-assembled nanodielectric (SAND) as the gate dielectric, the device mobilities and saturation current can be further improved up to 2560 cm2 V−1 s−1 and 160 μA, respectively. All devices exhibit good optical transparency (∼81% on average) in the visible spectral range. In addition, the nanowire TTFTs were utilized to control green OLEDs with varied intensities. Furthermore, a fully integrated seven-segment AMOLED display was fabricated with a good transparency of 40% and with each pixel controlled by two nanowire transistors. This work demonstrates that the performance enhancement possible by combining nanowire doping and self-assembled nanodielectrics enables silicon-free electronic circuitry for low power consumption, optically transparent, high-frequency devices assembled near room temperature.